Entrepreneurial Budgeting in the Iranian Government Budget: Obstacles and Solutions - Seyyed Mohammad Moghimi; Alireza Salmanian (مدیریت دولتی, 2024)
Objective The latest approach in budgeting is entrepreneurial budgeting, where strategic plans, motivational drivers, and accountability are integrated within the budget framework and connected to citizens as a whole package. The success of entrepreneurial budgeting is based on its previous performance budgeting, which requires articulating the mission, measurable objectives, performance actions for efficiency and effectiveness, and feedback loops for utilization through citizen satisfaction surveys and focused groups. Performance budgeting focuses on accountability and assigns responsibility to the heads of the organization and program managers. With sufficient accountability and performance indicators, policymakers can trust bureaucratic systems to decentralize budget spending authority. The budget is allocated to organization managers in a lump sum to manage it as they see fit. In return for this significant trust in government managers, it is expected that they provide evidence of success in their achievements based on their performance outcomes. In Iran and recent years, there has been a strong emphasis on moving towards budgeting based on performance budgeting, but generally, budgeting in Iran has usually been a combination of two types of budgeting, incremental and programmatic. It can be argued that due to the commonalities between performance-based budgeting and entrepreneurial budgeting, The endeavour towards entrepreneurializing the budget in the country not only does not conflict with past programs but will complement them. In the present study, initially, we seek to identify the obstacles to entrepreneurializing the government budget of Iran and secondly propose appropriate solutions. Methods The approach of this research is qualitatively analyzing the content by the analysis of data obtained from semi-structured interviews with 18 experts, practitioners, and stakeholders in public budgeting. In this research, initially, by using the library method and reviewing domestic and foreign books and articles, the theoretical foundations and research background will be examined. Then, the primary research data will be collected based on the research background and semi-structured interviews and the interview information will be coded. Results Obstacles to entrepreneurial budgeting of the Iranian government fall into five legal groups (gap between budget and upper-level documents, inflexibility of laws, weakness of tax laws, lack of transparency, lack of review in budget-receiving organizations), regulatory (weak administrative structure, wrong organizational culture, lack of organizational entrepreneurship, lack of specialization and meritocracy, commandment of the system of nepotism). The legislative (relationship between parliament and government, structure of interests, technical competence of representatives, governance of local and regional perspectives), executive (oil rent, government inefficiency, technical and structural problems, governance of political and ideological perspectives, economic instability), and supervisory (traditional approach, multiple supervisory institutions, lack of universal supervision) have been classified; under each, the most important relevant issues are listed and explained Conclusion By analyzing the data obtained from interviews and reviewing and delving into the comprehensive themes, three components of governance structure, mismanagement of oil revenues, and weak domestic production and civil society can be identified as the roots of emerging problems and other obstacles in establishing entrepreneurial budgeting in the country. In this way, the solutions for establishing this budgeting system in the country pass through solving these issues.